Abrupt total iron binding capacity elevation in microcytic hypochromic anemia - Krishna, Konda Siva; Vignesh, Yenduri Hari Krishna; Shukoor Waseem, Shaik Abdul; Kumar, Aravapalli Sravan; Gottipatti, Satheesh S; Puttagunt, Sirnivas Babu (Indian Journal of Case Reports, 2025)
Iron deficiency is a leading global cause of anemia, responsible for approximately 841,000 deaths annually, with Africa and parts of Asia bearing 71% of the mortality burden. Key risk factors include heavy menstrual bleeding, pregnancy, and the post-partum period. Management typically involves oral iron supplementation, dietary changes, and intravenous iron therapy for severe cases. This report presents the case of a 48-year-old woman diagnosed with iron deficiency anemia and Vitamin B12 deficiency. She exhibited microcytic hypochromic anemia confirmed by a peripheral smear, which revealed characteristic red blood cell morphology. The case underscores the importance of early detection and management of iron and Vitamin B12 deficiencies to prevent complications. It also highlights the need to address healthcare disparities that limit access to diagnostic and treatment options in underserved regions.